2023
DOI: 10.1186/s12888-023-04716-w
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime posttraumatic stress disorder as a predictor of mortality: a systematic review and meta-analysis

Abstract: Background Posttraumatic Stress Disorder (PTSD) could potentially increase the risk of mortality, and there is a need for a meta-analysis to quantify this association. This study aims to determine the extent to which PTSD is a predictor of mortality. Methods EMBASE, MEDLINE, and PsycINFO were searched systematically on 12th February 2020, with updated searches conducted in July 2021, and December 2022 (PROSPERO CRD42019142971). Studies involving co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 82 publications
0
7
0
2
Order By: Relevance
“…Зокрема, в учасників бойових дій, поширеність ПТСР становить від 12% до 30% порівняно з ризиком 7,8% серед загального населення США [17]. У пацієнтів із ПТСР спостерігається підвищений рівень смертності, який у 2-3 рази перевищує аналогічний у загальній популяції [18]. ПТСР корелює з незадовільним фізичним здоров'ям, приєднанням і прогресуваням ССЗ [19].…”
Section: посттравматичний стресовий розлад і метаболічний синдромunclassified
“…Зокрема, в учасників бойових дій, поширеність ПТСР становить від 12% до 30% порівняно з ризиком 7,8% серед загального населення США [17]. У пацієнтів із ПТСР спостерігається підвищений рівень смертності, який у 2-3 рази перевищує аналогічний у загальній популяції [18]. ПТСР корелює з незадовільним фізичним здоров'ям, приєднанням і прогресуваням ССЗ [19].…”
Section: посттравматичний стресовий розлад і метаболічний синдромunclassified
“…Lipids are emerging as an important contributor of health of the brain but the relationship between PTSD severity and lipid metabolites is unknown. While prior studies have found alterations in neuroendocrine, immune, and aging processes in PTSD 413 , our understanding of the role of metabolite disturbances in PTSD is limited.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, greater rapid eye movement sleep is found in women with PTSD compared to healthy controls, a difference not seen in men 3 . PTSD is also known to affect physical health and has been associated with greater inflammation, metabolic syndrome, gastrointestinal illness, and even early mortality 413 . It is possible that disturbed sleep may play a role in these health impacts since sleep duration correlates with metabolic risk in PTSD 14 .…”
Section: Introductionmentioning
confidence: 99%
“…While activation of these systems is beneficial under normal circumstances, excessive or prolonged stimulation is maladaptive, resulting in adverse biological effects on the body and brain. Indeed, it is now clear that stress is an important risk factor for a range of diseases [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%